Disseminated cryptococcosis, invasive aspergillosis, and mucormycosis in a patient treated with alemtuzumab for chronic lymphocytic leukaemia. (March 2014) - Henn, Aurélia; Mellon, Guillaume; Henry, Benoît; Roos-Weil, Damien; Jauréguiberry, Stéphane; Mordant, Pierre; Fekkar, Arnaud; Caumes, Eric
Abstract We report the case of a 42-y-old man treated with alemtuzumab for chronic lymphocytic leukaemia, who developed 3 successive deep fungal infections. Despite being treated with liposomal amphotericin B and 5-flucytosine for disseminated cryptococcosis, he developed pulmonary invasive aspergillosis, followed by pulmonary mucormycosis. Several deep fungal infections may occur in association in an immunocompromised host after treatment with alemtuzumab.